2017
DOI: 10.1016/j.irfa.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Monetary policy, bank lending and corporate investment

Abstract: The purpose of this study is to shed light on the chain of causality from macroeconomic financial policy to the microeconomic investment function. Concretely, we aim to provide an in-depth analysis of the relationships between the monetary policy of central banks, the loan policy of commercial banks, and the investment behavior of firms. We focus on countries that conduct their monetary policy under the inflation-targeting framework. Our empirical analysis with data from Germany, Switzerland and Thailand provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 48 publications
2
9
0
1
Order By: Relevance
“…With only bank fixed effects, two bank-level factors which are the equity ratio (EQUITYTA) and operating performance (ROA) have significant association with bank loans. These findings are generally in line with the findings of Vithessonthi et al (2017).…”
Section: The Effect Of Interest Rates On Supply Of Bank Loanssupporting
confidence: 91%
See 3 more Smart Citations
“…With only bank fixed effects, two bank-level factors which are the equity ratio (EQUITYTA) and operating performance (ROA) have significant association with bank loans. These findings are generally in line with the findings of Vithessonthi et al (2017).…”
Section: The Effect Of Interest Rates On Supply Of Bank Loanssupporting
confidence: 91%
“…Consistent with the regression results, it can be suggested that the monetary policy affects banks' lending rate in Turkey in the short-run (within three months). This finding supports the findings of Vithessonthi et al (2017) who determined that after controlling for the US monetary policy, the monetary policy in Germany and Thailand appears to influence banks' lending rate in the short-Business and Economics Research Journal, 10(2):313-326, 2019 N. Turguttopbas run (i.e. within two months), but not in Switzerland.…”
Section: The Effect Of Monetary Policy On Interest Ratessupporting
confidence: 86%
See 2 more Smart Citations
“…They constructed their own index of financial constraints, but because of shortcomings provided in the paper, they would like to conduct future research into the topic. Vithessonthi et al (2017) conducted a study focused on monetary policy, bank lending and corporate investment. They aimed to answer the question if monetary policy affects corporate investment in countries that use inflation targeting.…”
Section: Literature Reviewmentioning
confidence: 99%